Linear Equation System Study on Electrical Circuits Using Matlab - Ulul Ilmi (Universitas Islam Lamongan, 2018)
In everyday life, especially in the electrical circuit, there are many usage of matrix. One use of a matrix is found in the system of linear equations. In the field of electrical circuits there are also problems involving systems of linear equations in matrix form. To solve the system of linear equations in matrix form, in addition to using elementary row operations, also used matlab.